Numerical and Experimental Assessment of Mechanical Properties of Biobased Epoxy Reinforced by Flax Fibres and Seashell Nanoparticles for Prosthetic Socket. (14th September 2022) - Hadi, Ahmed Namah; Mohammed, Mohammed Razzaq; Al-Bakri, Amir F.
Abstract : Chronic diseases such as peripheral vascular and arteriosclerosis, wars, terrorist attacks, natural disasters, and traffic collisions are the major causes of the high demand for prostheses. The inadequacy of the typically used materials at reasonable prices and the high stiffness of these materials, which can negatively influence socket-limb load transfer, imply an urgent need to find alternatives to the existing prosthetic sockets. This work aims to use renewable, low-hazard, and low-cost natural flax fibres and seashell nanoparticles as substitutes for conventional reinforcement materials for prosthetic sockets. Seashell nanoparticles of 1, 3, and 5 weight fractions and 3 layers of flax fibres were integrated into biobased epoxy. Tensile and flexural properties of modified and unmodified specimens were assessed, and the finite element technique (ANSYS-20) was utilised to analyse and evaluate the mechanical characteristics of the specimens by observing the stress and total deformation. Here, all fabricated nanocomposites provided tensile and flexural strength higher than that of additive-free biobased epoxy. In addition, hybrid nanocomposites fabricated from 3 layers of flax fibres and 3 wt% of seashell nanoparticles were revealed to have the highest mechanical properties compared with unmodified resin and biobased epoxy filled with other percentages of the reinforcement. These findings were further validated numerically in which the total deformation was shown to decrease after the addition of 3 wt% of these nanoparticles within the nanocomposites. Moreover, the antibacterial activity proved its superb antimicrobial performance against various pathogenic microorganisms, namely, Staphylococcus aureus and E. coli . Accordingly, the fabricated composite systems are suggested to be an appropriate candidate for forming prosthetic sockets. These composites have promising mechanical and antibacterial properties, and they are made of affordable and available materials, which can be a suitable option, particularly in poor countries due to the fact that advanced technologies may require a substantial amount of money for equipment, surgery fees, and medical care.